2017
DOI: 10.1021/acs.chemmater.7b04516
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity and Octahedral Tilting in Hybrid Vacancy-Ordered Double Perovskites

Abstract: The advantageous performance of hybrid organic–inorganic perovskite halide semiconductors in optoelectronic applications motivates studies of their fundamental crystal chemistry. In particular, recent studies have sought to understand how dipolar, dynamic, and organic cations such as methylammonium (CH3NH3 +) and formamidinium (CH­(NH2)2 +) affect physical properties such as light absorption and charge transport. To probe the influence of organic–inorganic coupling on charge transport, we prepared the series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(176 citation statements)
references
References 89 publications
(152 reference statements)
13
157
1
Order By: Relevance
“…It was found that, in MASnI 3 , Sn 2+ can easily be oxidized to Sn 4+ and replacing MA with FA can reduce the extent of Sn oxidation. The origins of the relative stability are not clear, yet it is possible that this relates to the thermodynamic stability of the corresponding oxidized products, MA 2 SnI 6 and FA 2 SnI 6 , with the latter being more stable than the former, possibly due to the larger separation of the discrete [SnI 6 ] 2− octahedra. Moreover, FASnI 3 film exhibits a lower conductivity than MASnI 3 (Figure e).…”
Section: Properties Of Halide (I Br) Sn‐based Perovskite Materialsmentioning
confidence: 99%
“…It was found that, in MASnI 3 , Sn 2+ can easily be oxidized to Sn 4+ and replacing MA with FA can reduce the extent of Sn oxidation. The origins of the relative stability are not clear, yet it is possible that this relates to the thermodynamic stability of the corresponding oxidized products, MA 2 SnI 6 and FA 2 SnI 6 , with the latter being more stable than the former, possibly due to the larger separation of the discrete [SnI 6 ] 2− octahedra. Moreover, FASnI 3 film exhibits a lower conductivity than MASnI 3 (Figure e).…”
Section: Properties Of Halide (I Br) Sn‐based Perovskite Materialsmentioning
confidence: 99%
“…70,71 Recent studies have shown that the carrier mobilities of A 2 ,BX 6 could be further decreased in the case of any dynamic and/or static octahedral tilting. 72,73 On the other hand, for optical properties, because of the inversion symmetry, the transition from the VBM to the CBM is dipole forbidden, making the optical bandgap larger than the fundamental bandgap. 74 51 which may provide reasonably small bandgaps for single-junction solar cell applications.…”
Section: Vacancy-ordered Double Perovskitesmentioning
confidence: 99%
“…Moreover, the optoelectronic properties can be further tuned by replacing the Cs + cation on the A site with an organic ligand such as NH 4 + or CH 3 NH 3 + . Specifically, the electronic structure can be effectively modified via coupling the ligands to the rotational dynamics of [BX 6 ] 2− octahedral units through the enhanced hydrogen‐bonding interactions with the surrounding X‐site framework . Clearly, such findings demonstrate that the optical properties of HDPs are strongly related to the specific crystal structures.…”
Section: Introductionmentioning
confidence: 97%